The Profile of Consumer of Contemporary Lithuania - Leonavičius, Vylius (Sociologija. Mintis ir veiksmas, 2002)
The paper analyzes the data of survey which was carried out in Novermber-December 2001. The pattern of consumer society is applied for the analysis of the data. There are two general features of consumer society: it is whealthy and it has a set of characteristic values. The data shows that society in Lithuania has several characteristic features which differ it from typical wealthy western consumer society. At the same time it has some features which are related with wealthy society. First of all, the Lithuanian society is not the typical wealthy society. And the possibilities of population to consume are low. At the same time a part of society has values which are characteristic to the middle-class society: the need of self-expression and ecological attitudes.